Dominasi Asing dalam Agresivitas Pajak di Indonesia - Siti Maisaroh; Heru Tjaraka; Alfa Rahmiati (Politeknik Ganesha Medan, 2024)
This research aims to provide empirical evidence of the impact of foreign entities on tax aggressiveness in Indonesia. The sample consists of non-financial companies listed on the Indonesia Stock Exchange from 2017 to 2019, totaling 804 firm-years. The independent variables include foreign dominance represented by foreign share ownership, significant foreign share ownership, foreign commissioners, foreign directors, foreign CEOs, and foreign CFOs in these companies, while the dependent variable is tax aggressiveness. The results indicate that foreign ownership and significant foreign ownership do not have a significant influence on aggressive tax avoidance practices, contrary to previous research findings. However, another intriguing finding is that the composition of foreign commissioners and foreign directors has a significant impact on aggressive tax avoidance. The presence of foreign commissioners and directors appears to lead to increased compliance with tax regulations and a reduction in aggressive tax avoidance practices. This can be attributed to considerations of legal risk, reputation, and higher tax planning costs in the context of multinational corporations. These results provide valuable insights into the role of board composition in managing a company's tax practices. Overall, the findings contribute significantly to understanding the factors influencing aggressive tax avoidance practices in Indonesian companies, which can serve as a basis for more effective tax policies in the future. However, it is essential to note that this study has limitations and further research is needed to gain a deeper understanding of the dynamics of tax practices in an ever-evolving business environment.